Multisensory Model: Implementation and Contribution of Home Early literacy Stimulation - Ruhaena, Lisnawati; Moordiningsih, Moordiningsih (Jurnal Psikologi, 2019)
A multisensory model was implemented to improve the stimulation and development of early literacy skill. This implementation was conducted on 56 mothers and their children aged 3-5 years old, by giving them literacy media and assistance to the mothers. The assistance was carried out by 21 literacy ambassadors. Each literacy ambassador helped 2-3 mothers. Mixed-Method Action Research (MMAR) was conducted to implement the multisensory model and evaluate its contribution. Quantitative data were collected by scales, while qualitative data were collected by observation, interviews, and questionnaires. Quantitative data analysis was done with Paired Sample T-Test, and qualitative data analysis was conducted with content analysis. Once the multisensory model was applied, the stimulation of children's literacy shifted from a textual way to a contextual way. Multisensory models contributed to creating a storybook reading routine and playing hand puppets, letter cards, and activity books. This contribution was very important because it significantly increased literacy activity and developed children’s literacy skill.